Repeated exposure of house dust mite induces progressive airway inflammation in mice: Differential roles of CCL17 and IL‐13 - Ravi Malaviya; Zhao Zhou; Holly Raymond; Josh Wertheimer; Brian Jones; Rachel Bunting; Patrick Wilkinson; Lohith Madireddy; LeRoy Hall; Mary Ryan; Tadimeti S. Rao (Wiley, 2021)
Abstract We conducted a systematic evaluation of lung inflammation indued by repeated intranasal exposure (for 10 consecutive days) to a human aeroallergen, house dust mite (HDM) in BALB/c mice. Peak influx of neutrophils, monocytes/lymphocytes, and eosinophils was observed in bronchoalveolar lavage (BAL) on days 1, 7 and 11, respectively, and normalized to baseline by day 21. Peak elevations of Th2, myeloid‐derived cytokines/chemokines and serum IgE were seen both in BAL and lung tissue homogenates between days 7 and 11, and declined thereafter; however, IL‐33 levels remained elevated from day 7 to day 21. Airway hyperreactivity to inhaled methacholine was significantly increased by day 11 and decreased to baseline by day 21. The lung tissue showed perivascular and peribronchial cuffing, epithelial hypertrophy and hyperplasia and goblet cell formation in airways by day 11, and resolution by day 21. Levels of soluble collagen and tissue inhibitors of metalloproteinases (TIMP) also increased reflecting tissue remodeling in the lung. Microarray analysis demonstrated a significant time‐dependent up‐regulation of several genes including IL‐33, CLCA3, CCL17, CD4, CD10, CD27, IL‐13, Foxa3, IL‐4, IL‐10, and CD19, in BAL cells as well as the lung. Pre‐treatment of HDM challenged mice with CCL17 and IL‐13 antibodies reduced BAL cellularity, airway hyper‐responsiveness (AHR), and histopathological changes. Notably, anti‐IL‐13, but not anti‐CCL17 monoclonal antibodies (mAbs) reduced BAL neutrophilia while both mAbs attenuated eosinophilia. These results suggest that CCL17 has an overlapping, yet distinct profile versus IL‐13 in the HDM model of pulmonary inflammation and potential for CCL17‐based therapeutics in treating Th2 inflammation.